Two new combinations in Iberian Santolina (Compositae) based on morphology and molecular evidences - Carbajal, Rodrigo; Serrano, Miguel; Ortiz, Santiago; Sáez, Llorenç (Phytotaxa, 2017)
The genus Santolina is represented in the Iberian Peninsula and Balearic Islands mainly by two complexes of species: S. rosmarinifolia aggr. and S. chamaecyparissus aggr., with a great similarity between the taxa included in each of these complexes. In the study of Santolina for the “Flora iberica” project, we prefer the species rank for the taxa with main differences in foliar and involucral bracts. Two new combinations, S. vedranensis and S. montiberica, are proposed here on the basis of our morphological analysis and on evidences from our ongoing molecular studies.